Delimitação do mercado relevante geográfico para produtos asfálticos - Garcia, Ana Carolina Della Colletta (Universidade Federal de São Carlos, 2015)
The aim of this work is the use of price test method to determine the geographic relevant market, so that if two geographic areas form a single geographical market for a given product, in the long term, the price trajectory between these regions would follow the same path. The empirical application was made to the asphalt products distributors market in Brazil, more specifically for asphalt cement and diluted asphalt, for the period between January 2008 and December 2014. Due to increasing demand of asphalt products for maintenance and conservation of the existing road network and the creation of new roads, besides the existence of few studies defining the relevant market in order to evaluate a possible market power of the distributors of such products, becomes of utmost importance to make further studies. It is concluded that the relevant market for these products is National, except Northeast for asphalt cement.
Delimitation ofthe relevant market geographical to asphalt products
Keywords: Testes - preços; Tests - prices; Mercados; Markets; Asfalto; Asphalt; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL